Femtosecond pump probe spectroscopy of light harvesting complexes and Phthalocyanines - Ombinda-Lemboumba, Saturnin (Stellenbosch : Stellenbosch University, 2011)
Thesis (PhD)--Stellenbosch University, 2011.